Strategi Pemasaran Digital Melalui Instagram pada Usaha DEF Laundry: Perancangan dan Implementasi - Faizah Yusriyah; Shelly Pramudiawardani; Rusmanto Rusmanto (DBESTI: Journal of Digital Business and Technology Innovation, 2026)
DEF Laundry is a laundry service business located in Bojonggede. This business faces challenges in implementing digital marketing, particularly in utilizing social media. This study aims to design and implement a digital marketing strategy for DEF Laundry using Instagram, as well as to identify the types of promotional content that can attract customer interest in choosing DEF Laundry's services. Using a qualitative-correlational and descriptive approach, data were collected through interviews and validated through data triangulation. The results show that the digital marketing strategy designed using the STP approach and SWOT analysis successfully identified a relevant market segment. The implementation of promotional content was considered effective, as it conveyed service information clearly and attracted audience attention. Moreover, customer decisions regarding the use of DEF Laundry's services were influenced by three main factors: service quality, access to clear information, and appealing digital promotional strategies. The digital marketing strategy implemented through Instagram proved effective in increasing customer interest. The informative and interactive promotional content supported the customer's decision-making process. Thus, this strategy can serve as a solution to support the digitalization of DEF Laundry's promotional efforts in the social media era.